Simulation and Characterization of Microdilution Chip - Mazlan, Nurhaslinda; Abd Hamid, Intan Sue Liana (Evolution in Electrical and Electronic Engineering, 2021)
Extraction liquid methods is currently being applied in various of fields such as biochemical engineering, biochemistry, and biology applications. In this work, a microdiluter chip is designed and simulated for simultaneously carrying out multiple solution with different concentrations. There are four set solutes used in this project which are water/heptane, water/ethanol, water/glycerol, and water/diethyl ether. The COMSOL software used in this work produce a precise result of microdiluter that is able to produce 30%, 70%, 80%, 90% and 100% of dilution.